2017
DOI: 10.1038/aps.2016.167
|View full text |Cite
|
Sign up to set email alerts
|

Insights into molecular therapy of glioma: current challenges and next generation blueprint

Abstract: Glioma accounts for the majority of human brain tumors. With prevailing treatment regimens, the patients have poor survival rates. In spite of current development in mainstream glioma therapy, a cure for glioma appears to be out of reach. The infiltrative nature of glioma and acquired resistance substancially restrict the therapeutic options. Better elucidation of the complicated pathobiology of glioma and proteogenomic characterization might eventually open novel avenues for the design of more sophisticated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 144 publications
(116 reference statements)
0
75
0
1
Order By: Relevance
“…The results revealed that participate in colorectal cancer, prostate cancer, pancreatic cancer, glioma, and other cancer-related pathways. Among these, MAPK, Wnt, and mammalian target of rapamycin (mTOR) signaling pathways are closely related to glioma occurrence and development [49]. These signaling cascades primarily down-regulate tumor-suppressor genes and up-regulate tumor-causing genes in glioma [11, 15, 50-52].…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that participate in colorectal cancer, prostate cancer, pancreatic cancer, glioma, and other cancer-related pathways. Among these, MAPK, Wnt, and mammalian target of rapamycin (mTOR) signaling pathways are closely related to glioma occurrence and development [49]. These signaling cascades primarily down-regulate tumor-suppressor genes and up-regulate tumor-causing genes in glioma [11, 15, 50-52].…”
Section: Discussionmentioning
confidence: 99%
“…However and in many cases; chemotherapy of those tumors is problematic; as the anticancer drugs are often hydrophobic molecules leading to restricted access to brain tissues [55]. Even though accompanied by severe side effects; a combination of surgery; radiotherapy and the use of chemotherapeutical drugs [31,32,56] remain the main options in treatment of those tumors [57]. In that context; the alkylating prodrug temozolomide crosses the blood-brain barrier (BBB) and disintegrates spontanously (non-enzymatic) in methyl hydrazine which alkylates DNA bases finally resulting in inhibition of DNA replication and in triggering of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this particular analysis, we decided to concentrate on three types of molecular data, one discrete (somatic mutations) and two -continuous (RNA-seq gene expression, and promoter methylation). This selection is reflective of the recent trends in multimodal cancer data analyses [21,26], makes sense in the broad cancer genetics context [27][28][29][30][31][32], and underscores the comparative importance of the methylation molecular data [29].…”
Section: Introductionmentioning
confidence: 97%